A promising protein responsible for overactive bladder in ovariectomized mice - Huey-Yi Chen; Chao-Jung Chen; Wen-Chi Chen; Shih-Jing Wang; Yung-Hsiang Chen (Elsevier, 2017)
Objective: Ovariectomy (OVX) in mice is a model mimicking a neuro-electronic proof of an overactive bladder in postmenopausal women. Overactive bladder (OAB) was recently found to be due to an altered gap junction protein in a rat model. Thus, this study was conducted to evaluate changes in cell junction protein expression and composition in the bladder of OVX mice. Materials and Methods: Thirty-six virgin female mice were randomized into three groups: mice with a sham operation only (control), OVX mice without estradiol (E2) replacement, and OVX mice with E2 replacement (OVX + E2). Cystometry assessment was conducted and cell junction-associated protein zonula occludens-2 (ZO-2) expression was measured after 8 weeks. Voiding interval values (time between voids) were assessed in mice under anesthesia. After measurements, the bladders were removed for proteomic analysis using the label-free quantitative proteomics and liquid chromatography-mass spectrometry technology. Lastly, immunohistochemistry (IHC) and Western blot were used to confirm the location and level, respectively, of ZO-2 expression. Results: We identified 73 differentially expressed proteins in the bladder of OVX mice. The OVX mice showed significantly lower voiding interval values. Voiding interval values were significantly higher in the OVX + E2 group than in the OVX group. Urothelial thicknesses in the bladder were also significantly lower in the OVX group than in the control group. E2 replacement reversed the urothelium layers. Additionally, the expression of ZO-2, a tight junction protein, was the most affected by OVX treatment. IHC and Western blot confirmed the downregulation of ZO-2 in the bladder of OVX mice. Expression of ZO-2 protein was significantly increased in OVX + E2 group compared with OVX group. Conclusion: This exploratory study estimated changes in protein expression and composition in the bladder of OVX mice. These changes may be associated with the molecular mechanisms of OAB.